1996
DOI: 10.1111/j.1365-2265.1996.tb02061.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and pharmacodynamics of subcutaneous testosterone implants in hypogonadal men

Abstract: T-pellets are the androgen formulation with the longest biological action and strongest pharmacodynamic efficacy in terms of gonadotrophin suppression. The pharmacokinetic features are advantageous compared to other T preparations and the patient acceptance is high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
41
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 38 publications
(58 reference statements)
6
41
0
1
Order By: Relevance
“…75,76 The standard dosage is four 200 mg pellets (800 mg) implanted subdermally at intervals of 5 to 7 months. 77 Yet the in vivo testosterone release rate of these testosterone pellets and its determinants have not been studied systematically.…”
Section: Subdermal Implantsmentioning
confidence: 99%
“…75,76 The standard dosage is four 200 mg pellets (800 mg) implanted subdermally at intervals of 5 to 7 months. 77 Yet the in vivo testosterone release rate of these testosterone pellets and its determinants have not been studied systematically.…”
Section: Subdermal Implantsmentioning
confidence: 99%
“…Male mice with targeted disruption of the nNOS gene (nNOS Ϫ ) display a great increase in aggressive behavior and excessive and inappropriate mounting behavior (11). Because androgens also promote aggressive behavior (23,24), facilitate mounting behavior (25,26), and decrease gonadotropin release (27,28), we wanted to elucidate whether the androgens, testosterone (T) and its 5␣ reduced metabolite, dihydrotestosterone (DHT), modulate nNOS activity in the brain and the potential mechanism(s) by which this may occur.…”
mentioning
confidence: 99%
“…The possibility of extrusion, although rare, also exists (40). A review of 13 years of experience in subdermal testosterone implantation in 221 men showed limited adverse local effects (11% of total 973 consecutive implants) such as extrusion, bleeding, and inflammations/infections.…”
Section: Subcutaneous Implantsmentioning
confidence: 96%